ANALISIS KURIKULUM MERDEKA BELAJAR KAMPUS MERDEKA DI MTS ISLAMIYAH MEDAN - Setiawan, Imam; Munawir Pasaribu (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The study aims to analyze the independent curriculum (MBKM) implemented at MTs Islamiyah Medan through development of prodessional abilities. Merdeka Belajar is an Indonesia government initiative in realizing higher education that inclusive and relevant to industry needs. In the context of MTs Islamiyah Medan, the Merdeka Belajar curriculum is a reference for students to develop competencies and skills needed in the world of work and everyday life. This study uses a qualitative approach with a case study method. Data was collected through participatory observation, in-depth interviews and document analysis. The results showed that the implementation of the Merdeka Belajar at MTs Islamiyah Medan has made a positive contribution to improving the quality of learning and student’s readiness to face future challenges. Through field practice in schooling, students’ have the opportunity to integrate theory with practice in the real world so that they can develop social, skills of communication, and problem solving effectively. But, several challeng’s were found in the implementation of the Merdeka Belajar curriculum, including limited resources and adequate support for the implementation of development of professional abilities., there are some differences among educators regarding this curriculum,which requires better harmonization and communication efforts to achieve the expected goals.